Differences in Circulating Non-Transferrin-Bound Iron after Oral Administration of Ferrous Sulfate, Sodium Iron EDTA, or Iron Polymaltose in Women with Marginal Iron Stores. Issue 2 (June 2013) - Schümann, Klaus; Solomons, Noel W.; Orozco, Monica; Romero-Abal, Maria Eugenia; Weiss, Guenter
Background: The adverse interactions between iron supplements and malaria have driven the assessment of new therapeutic options for anemia prophylaxis in areas holoendemic for falciparum malaria. Objective: To determine the responses of circulating non-transferrin-bound iron (NTBI) and plasma iron to three different oral iron compounds—ferrous sulfate, sodium iron ethylenediaminetetraacetate (NaFeEDTA), and iron polymaltose (IPM)—in women with marginal iron stores. Methods: Serum samples from 10 Guatemalan women with marginal iron stores were collected every 90 minutes over a period of 270 minutes, after the individually randomized administration of 100 mg of iron from each of the three studied iron compounds or water alone. Serum iron concentration was quantified by the ferrozine method, and circulating NTBI concentration was determined with a fluorometric competitive binding assay. Kinetic responses and maximal cumulative changes in serum concentrations of iron and NTBI were compared between the four treatments. Comparison was made with data from the same protocol in iron-adequate men. Results: The serum iron and NTBI responses to ferrous sulfate were significantly greater than those to water and the other two iron compounds. Serum iron responses to IPM did not differ from those to water alone. Conclusions: The administration of the two "slow-release" iron compounds, NaFeEDTA and IPM, resulted in a highly significant suppression of the appearance of NTBI in the circulation in the postsupplement period. These two bioavailable forms of iron supplement could represent a safe option for supplementation in malarial areas. The slope of the iron—NTBI relationship is steeper in men than in women.